„Desine gentilibus iam inservire poetis…” (versus XI 9). Chrześcijańscy epicy w bibliotece Izydora z Sewilli - Krynicka, Tatiana (Vox Patrum, 2013)
Isidore of Seville (560-636) is rightly considered to be one of the most important teachers of the medieval Europe. He wrote numerous didactic works on catholic doctrine, biblical exegesis, history, grammar, natural sciences etc. Isidore was neither a scientist nor an independent thinker, but indeed he was a genius of compilation. He spent his youth in the famous library of the bishops of Seville, where he stored knowledge by studying Holy Scriptures and works of classic and Christian authors. This library was destroyed, but we could strive to recreate its catalogue reading the books written by Isidore. In his Versus in bibliotheca Isidore tells us about authors he knew. We find among them Christian poets – Prudentius, Iuvencus, Sedulius, Avitus Viennensis. In Etymologiae Isidore presents to the reader Dracontius, and in De viris illustribus he admires talents of the centonist Proba. Isidore’s knowledge of Christian epics and the high regard he had for them tell us a lot not only about literary tastes of the well-educated bishop, but about the culture of reading of inhabitants of Visigothic Spain in the seventh century as well.